Planet Hunters TESS IV: a massive, compact hierarchical triple star system TIC 470710327. Issue 4 (2nd March 2022) - Eisner, N L; Johnston, C; Toonen, S; Frost, A J; Janssens, S; Lintott, C J; Aigrain, S; Sana, H; Abdul-Masih, M; Arellano-Córdova, K Z; Beck, P G; Bordier, E; et al.
ABSTRACT: We report the discovery and analysis of a massive, compact, hierarchical triple system (TIC 470710327) initially identified by citizen scientists in data obtained by NASA's Transiting Exoplanet Survey Satellite ( TESS ). Spectroscopic follow-up observations obtained with the hermes spectrograph, combined with eclipse-timing variations (ETVs), confirm that the system is comprised of three OB stars, with a compact 1.10 d eclipsing binary and a non-eclipsing tertiary on a 52.04 d orbit. Dynamical modelling of the system (from radial velocity and ETVs) reveal a rare configuration wherein the tertiary star (O9.5-B0.5V; 14–17 M⊙ ) is more massive than the combined mass of the inner binary (10.9–13.2 M⊙ ). Given the high mass of the tertiary, we predict that this system will undergo multiple phases of mass transfer in the future, and likely end up as a double neutron star gravitational wave progenitor or an exotic Thorne–Żytkow object. Further observational characterization of this system promises constraints on both formation scenarios of massive stars as well as their exotic evolutionary end-products.